Negative regulation of Wingless signaling by D-axin, a Drosophila homolog of axin. - Hamada, F.; Tomoyasu, Y.; Takatsu, Y.; Nakamura, M.; Nagai, S.; Suzuki, A.; Fujita, F.; Shibuya, H.; Toyoshima, K.; Ueno, N.; Akiyama, T. (Science, 1999)
Wnt/Wingless directs many cell fates during development. Wnt/Wingless signaling increases the amount of beta-catenin/Armadillo, which in turn activates gene transcription. Here the Drosophila protein D-Axin was shown to interact with Armadillo and D-APC. Mutation of d-axin resulted in the accumulation of cytoplasmic Armadillo and one of the Wingless target gene products, Distal-less. Ectopic expression of d-axin inhibited Wingless signaling. Hence, D-Axin negatively regulates Wingless signaling by down-regulating the level of Armadillo. These results establish the importance of the Axin family of proteins in Wnt/Wingless signaling in Drosophila.